THE USE OF STICKY NOTES IN READING MATERIALS TO IMPROVE ESP LEARNERS’ VOCABULARIES - Nur Laili Indasari; Nor Mubin (Atthiflah: Journal of Early Childhood Islamic Education, 2023)
The aims of this study are to describe the implementation of Sticky Notes (SN) in details, to reveal the improved aspects on English skill, and to express English for a Specific Purpose (ESP) learners’ experience after the use of SN. To explain the improvements, it was used classroom action research (CAR) design which was conducted in two cycles. The participants were eleven ESP students who took Early Childhood Islamic Education department. The data were obtained through observation, students’ test, and interview. The results of study showed that 8 of 9 students gave positive response toward the implementation of SN in reading materials. It was also revealed that applying SN in reading materials had advantages and disadvantages. The advantages from the side of English aspects were the enhancement of students’ memory, vocabulary, pronunciation, and reading comprehension. Meanwhile, the disadvantages from the side of medium (SN) itself were appearance and durability. However, all students agreed that the use of SN can enhance their English skills. These findings can be used as an input for lecturer in teaching